Ndr2 Kinase Controls Neurite Outgrowth and Dendritic Branching Through α1 Integrin Expression - Demiray, Yunus E.; Rehberg, Kati; Kliche, Stefanie; Stork, Oliver (Frontiers in Molecular Neuroscience, 2018)
The serine / threonine kinase Ndr2 has been shown to control the inside-out activation of the β1 subunit of integrins and the formation of neurites in both primary neurons and neurally differentiated pheochromacytoma (PC12) cells. In this study, we demonstrate that Ndr2 kinase furthermore determines the substrate specificity of neurite extension in PC12 cells via expression of α1β1 integrins. We show that stable overexpression of Ndr2 in PC12 cells increases neurite growth and extension on poly-D-lysine substrate, likely involving an increased expression of active β1 integrin in the growth tips of these cells. By contrast, the Ndr2 overexpressing cells do not show the α1β1 integrin-mediated enhancement of neurite growth on collagen IV substrate that can be seen in control cells. Moreover, they entirely fail to increase in response to activation of α1β1 integrins via a soluble KTS ligand and show a diminished accumulation of α1 integrin in neurite tips, although the expression of this subunit is induced during differentiation to comparable levels as in control cells. Finally, we demonstrate that Ndr2 overexpression similarly inhibits the α1β1 integrin-dependent dendritic growth of primary hippocampal neurons on laminin 111 substrate. By contrast, lack of Ndr2 impairs the dendritic growth regardless of the substrate. Together, these results suggest that Ndr2 regulates α1 integrin trafficking in addition to β1 integrin subunit activation and thereby controls the neurite growth on different extracellular matrix substrates.